2020
DOI: 10.1007/s00294-020-01143-2
|View full text |Cite
|
Sign up to set email alerts
|

Golden Gate vectors for efficient gene fusion and gene deletion in diverse filamentous fungi

Abstract: The cloning of plasmids can be time-consuming or expensive. Yet, cloning is a prerequisite for many standard experiments for the functional analysis of genes, including the generation of deletion mutants and the localization of gene products. Here, we provide Golden Gate vectors for fast and easy cloning of gene fusion as well as gene deletion vectors applicable to diverse fungi. In Golden Gate cloning, restriction and ligation occur simultaneously in a one-pot reaction. Our vector set contains recognition sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 74 publications
0
22
0
Order By: Relevance
“…For the construction of the pArp1-KO knockout plasmid, the Golden Gate cloning system according to Dahlmann et al, 2020, was used [ 57 ]. The 5′-(1311 bp) and 3′-(1791 bp) flanking regions of the Smarp1 gene were amplified from S. macrospora wt gDNA with the Arp1-ko-5f/Arp1-ko-5r and Arp1-ko-3f/Arp1-ko-3r primer pairs, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the construction of the pArp1-KO knockout plasmid, the Golden Gate cloning system according to Dahlmann et al, 2020, was used [ 57 ]. The 5′-(1311 bp) and 3′-(1791 bp) flanking regions of the Smarp1 gene were amplified from S. macrospora wt gDNA with the Arp1-ko-5f/Arp1-ko-5r and Arp1-ko-3f/Arp1-ko-3r primer pairs, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The 5′-(1311 bp) and 3′-(1791 bp) flanking regions of the Smarp1 gene were amplified from S. macrospora wt gDNA with the Arp1-ko-5f/Arp1-ko-5r and Arp1-ko-3f/Arp1-ko-3r primer pairs, respectively. Together with the donor vector pGG-hph and the destination vector pDest-Amp, the fragments were cloned via the Golden Gate procedure [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…All plasmids and primers (Sigma-Aldrich Chemie GmbH Taufkirchen, Germany) used in this study are shown in Tables S1 and S2 in Supplementary Materials . Plasmids were constructed via HR in S. cerevisiae [ 34 ] or the Golden Gate (GG) cloning system [ 45 ]. For p5′sci1-egfp_hyg, the S. macrospora sci1 native promotor and ORF and the trpC terminator ( TtrpC ) of Aspergillus nidulans were amplified from plasmid p5′sci1gfp_nat [ 14 ] with the primer pair 5′sci1-f/pRS426GFPrev.…”
Section: Methodsmentioning
confidence: 99%
“…To generate the knockout-plasmid pPom33-KO, the Golden Gate cloning system according to [ 45 ] was used. The 5′ (726 bp) and 3′ (1021 bp) flanking regions of the pom33 gene were amplified from S. macrospora wt gDNA with primer pairs Pom33-GG-ko-5f/Pom33-GG-ko-5r and Pom33-GG-ko-3f/Pom33-GG-ko-3r, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation